Sport techniques in physical education school: a look at the socio-cultural trends - Rodrigues, Heitor de Andrade [UNESP]; Darido, Suraya Cristina (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2008)
Teaching sports techniques lessons of Physical Education is a very controversial subject. We must emphasize the fact that called our attention, that dealing with sport in a critical way would be the same as being against the teaching of the art. Several factors contributed in shaping this reality, among them we suspect that the proposal's incomprehension made within the socio-cultural trends. Thus, the aim of this work was to investigate the technical aspects of sports in teaching of Physical Education, as socio-cultural trends part. Throughout the text it is possible to identify new goals considering sportive techniques such as the concern with interests of students who movement, consideration of cultural repertoire of these students, in addition to proposing that the lessons do not restrict implementation of these movements, but also includes the knowledge of social, political, economic and cultural universe of sports events.
Keywords: Teaching; Physical Education and training; Cultural Characteristics